Updates on hepatic homeostasis and the many tiers of hepatobiliary repair - Monga, Satdarshan P. (Nature reviews. Gastroenterology & hepatology, 2019)
Deciphering the complex circuitry of liver homeostasis and repair is required to improve regenerative therapies for hepatic diseases. Studies in 2018 have identified subsets of hepatic cells that have unique reparative abilities and clarified the role of biomechanical forces and hepatobiliary reprogramming as sustainable modes of tissue repair. Key advances Rare and random TERT High hepatocytes in all metabolic zones of a hepatic lobule represent a distributed model of hepatic homeostasis and regeneration 2 . Mechanosensing of altered blood flow by sinusoidal endothelial cells regulates the release of angiocrine factors that influence hepatocyte proliferation during development and regeneration 5 . Hepatocytes and cholangiocytes can transdifferentiate into each other to aid in hepatobiliary repair when an injury is chronic or excessive and prohibits survival and proliferation of the default cell type 8 – 10 .